Adaptiveness in proactive control engagement in children and adults. (December 2020) - Chevalier, Nicolas; Meaney, Julie Anne; Traut, Hilary Joy; Munakata, Yuko
Highlights: We examined efficiency of and adaptiveness in proactive control use as a function of contextual cue reliability in 6- and 9-year-olds and adults. All age groups showed greater behavioural, ERP and pupil dilation markers of proactive task selection when cues were reliable. Early developing use of contextual cue reliability ensures some degree of adaptiveness in proactive control engagement from 6 years onwards. Only adults additionally engaged in motor preparation with reliable precues, suggesting refinement in proactive control efficiency with age. Abstract: Age-related progress in cognitive control reflects more frequent engagement of proactive control during childhood. As proactive preparation for an upcoming task is adaptive only when the task can be reliably predicted, progress in proactive control engagement may rely on more efficient use of contextual cue reliability. Developmental progress may also reflect increasing efficiency in how proactive control is engaged, making this control mode more advantageous with age. To address these possibilities, 6-year-olds, 9-year-olds, and adults completed three versions of a cued task-switching paradigm in which contextual cue reliability was manipulated. When contextual cues were reliable (but not unreliable or uninformative), all age groups showed greater pupil dilation and a more pronounced (pre)cue-locked posterior positivity associated with faster response times, suggesting adaptive engagement of proactive task selection. However, adults additionally showed a larger contingent negative variation (CNV) predicting a further reduction in response times with reliable cues, suggesting motor preparation in adults but not children. Thus, early developing use of contextual cue reliability promotes adaptiveness in proactive control engagement from early childhood; yet, less efficient motor preparation in children makes this control mode overall less advantageous in childhood than adulthood.